A formação (Bildung) em Max Horkheimer - Para uma nova relação entre o ser humano e a natureza - Fontoura, Guilherme Vasconcelos (2021)
The broad concept of formation is a direct heir to ancient Greek culture, having played an important role in the consolidation of that society and the so-called Western culture. This concept finds its correlated in modernity through the term Bildung, denoting an ability to shape individuals for a full life in society. The modern experience, however, represented a resurgence of this sense of education, which gave way to the specialization and compartmentalization of the different fields of knowledge. His tradition, on the other hand, finds defense and reformulation of his precepts in the philosophy of Max Horkheimer. This philosopher, partly because of the historical context in which he is inserted (namely: the twentieth century, of the great international conflicts; of the rise of fascism; and of the scientific-industrial advance), partly because of the impetus that guides him to the philosophical commitment to investigate reality, brings important reflections on the formation that they find echo in the current context. Although the work does not count on reading a part of his writings on formation (Bildung), specifically those who do not find translation of the original in German, those who are contemplated, together with the support of other works of the philosopher and the reading of interpreters of his most general philosophy and, particularly, his relationship with formation (Bildung) allows us to structure an adequate verification of his treatment to the subject. In this sense, the research has a bibliographical analysis of several works of the philosopher and his commentators to elucidate the meaning of his considerations about formation (Bildung). By taking as a central aspect of his philosophy the relationship of the human being with nature, Horkheimer reveals the regressive aspect of technical-scientific progress that is imposed in the form of the domination of nature. The effects of this domination are visible to the philosopher in the form of a crisis of reason that results in the corrosion of ideas debuting to Western culture such as that of the individual, democracy, justice and freedom. This work aims to evaluate the role of formation (Bildung) in Horkheimer's philosophy and its transformative potential, since it is united with the philosophical work of constituting and, at the same time, criticizing the status of the relationship between theory and practice.